Room-temperature third-order nonlinear Hall effect in Weyl semimetal TaIrTe4. Issue 12 (14th February 2022) - Wang, Cong; Xiao, Rui-Chun; Liu, Huiying; Zhang, Zhaowei; Lai, Shen; Zhu, Chao; Cai, Hongbing; Wang, Naizhou; Chen, Shengyao; Deng, Ya; Liu, Zheng; Yang, Shengyuan A; et al.
Abstract: The second-order nonlinear Hall effect observed in the time-reversal symmetric system has not only shown abundant physical content, but also exhibited potential application prospects. Recently, a third-order nonlinear Hall effect has been observed in MoTe2 and WTe2 . However, few-layer MoTe2 and WTe2 are usually unstable in air and the observed third-order nonlinear Hall effect can be measured only at low temperature, which hinders further investigation as well as potential application. Thus, exploring new air-stable material systems with a sizable third-order nonlinear Hall effect at room temperature is an urgent task. Here, in type-II Weyl semimetal TaIrTe4, we observed a pronounced third-order nonlinear Hall effect, which can exist at room temperature and remain stable for months. The third-order nonlinear Hall effect is connected to the Berry-connection polarizability tensor instead of the Berry curvature. The possible mechanism of the observation of the third-order nonlinear Hall effect in TaIrTe4 at room temperature has been discussed. Our findings will open an avenue towards exploring room-temperature nonlinear devices in new quantum materials. Abstract : In a type-II Weyl semimetal TaIrTe4, the pronounced 3 rd order nonlinear Hall effect signal has been observed, which can exist at room temperature and remain stable for months.